Epoxylipids and soluble epoxide hydrolase in heart diseases - Imig, John D; Cervenka, Ludek; Neckar, Jan (Biochemical pharmacology, 2022)
Cardiovascular and heart diseases are leading causes of morbidity and mortality. Coronary artery endothelial and vascular dysfunction, inflammation, and mitochondrial dysfunction contribute to progression of heart diseases such as arrhythmias, congestive heart failure, and heart attacks. Classes of fatty acid epoxylipids and their enzymatic regulation by soluble epoxide hydrolase (sEH) have been implicated in coronary artery dysfunction, inflammation, and mitochondrial dysfunction in heart diseases. Likewise, genetic and pharmacological manipulations of epoxylipids have been demonstrated to have therapeutic benefits for heart diseases. Increasing epoxylipids reduce cardiac hypertrophy and fibrosis and improve cardiac function. Beneficial actions for epoxylipids have been demonstrated in cardiac ischemia reperfusion injury, electrical conductance abnormalities and arrhythmias, and ventricular tachycardia. This review discusses past and recent findings on the contribution of epoxylipids in heart diseases and the potential for their manipulation to treat heart attacks, arrhythmias, ventricular tachycardia, and heart failure.
Keywords: Coronary artery; Mitochondrial function; Arrhythmias, Cardiac; Fatty Acids; srdeční arytmie; inhibitory enzymů; lidé; epoxid hydrolasy; Humans; rozpustnost; infarkt myokardu; Heart Failure; Solubility; Hypertension; Animals; Tachycardia, Ventricular; Myocardial Infarction; nemoci srdce; Enzyme Inhibitors; Epoxide Hydrolases; zvířata; Myocardial infarction; Soluble epoxide hydrolase; epoxidové sloučeniny; mastné kyseliny; komorová tachykardie; Epoxy Compounds; srdeční selhání; Inflammation; Heart failure; Eicosanoids; Heart Diseases; Cytochrome P450